Tom Bullock: 173 Pre-Prohibition Cocktails - Jaine, Tom (Petits Propos Culinaires, 2024)
Tom Bullock: 173 Pre-Prohibition Cocktails: Howling at the Moon Press, Jenks, Oklahoma, 2001: ISBN 0-9654333-2-3: 173 pp., b/w photos, p/b, 14.95.